Cinema and experience : Siegfried Kracauer, Walter Benjamin, and Theodor W. Adorno - Hansen, Miriam, 1949-2011 (University of California Press, 2012)
Siegfried Kracauer, Walter Benjamin, and Theodor W. Adorno--affiliated through friendship, professional ties, and argument--developed an astute philosophical critique of modernity in which technological media played a key role. This book explores in depth their reflections on cinema and photography from the Weimar period up to the 1960s. Miriam Bratu Hansen brings to life an impressive archive of known and, in the case of Kracauer, less known materials and reveals surprising perspectives on canonic texts, including Benjamin's artwork essay. Her lucid analysis extrapolates from these writings the.
Keywords: Kracauer, Siegfried, -- 1889-1966 -- Criticism and interpretation.; Benjamin, Walter, -- 1892-1940 -- Criticism and interpretation.; Adorno, Theodor W., -- 1903-1969 -- Criticism and interpretation.; Adorno, Theodor W., -- 1903-1969; Benjamin, Walter, -- 1892-1940; Kracauer, Siegfried, -- 1889-1966; Motion pictures.; Cinéma.; ART -- Film & Video.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- General.; Motion pictures; 20th century cinema.; 20th century cultural critics.; 20th century photography.; american film history.; books for film enthusiasts.; books for movie critics.; cinema and photography.; cinema and technology.; cinema studies.; critical theory.; digital technology and film.; european philosophers.; evolution of cinema.; famous film critics.; film criticism.; film history.; film theorists.; history of digital technology.; history of movies.; motion picture history.; movie and video history.; technology and film.; technology.; Criticism, interpretation, etc.; Films.